In Situ Generated and Amplified Oxidative Stress with Metallo‐Nanodrug Assembly for Metastatic Cancer Therapy with High Specificity and Efficacy. Issue 11 (5th September 2021) - Hu, Jialing; Jiang, Qunying; Shi, Tianhui; Lin, Xue; Zhao, Yun; Wang, Xiuyuan; Liu, Xiaoqing
Abstract: Combination of anti‐metastasis antagonists with cytotoxic agents has shown clinical activity, yet is constrained with unconditional activation and low tumor selectivity. Here, a chemokine receptor‐targeted metallo‐nanodrug is reported for in situ generated and hyperthermia‐enhanced oxidative stress and metastatic pathway blockade with tumor specificity to treat breast cancer metastasis. The self‐assembled metallo‐nanodrugs trigger reactive oxygen species (ROS) generation in situ with tumor stimuli, self‐amplify ROS level upon intrinsic photothermal heating, and accurately block chemokine receptor CXCR4 to suppress tumor cell anti‐apoptosis, migration, and invasion. CXCR4‐targeted metallo‐nanodrugs plus laser irradiation induced complete inhibition of tumor growth in 80% of mice, and caused 92.8% reduction of the number of gross metastatic lung nodules in murine breast carcinoma models. The present work provides an intelligent and bioactivatable platform for precision nanomedicine of metastatic breast cancer. Abstract : Self‐assembled metallo‐nanodrugs trigger in situ ROS generation upon multiple biological stimuli, self‐amplify oxidative stress in response to light stimulus, and accurately target and block chemokine/chemokine receptor signaling pathway to alleviate breast cancer metastasis with high specificity and efficacy.